Afro-Catholic Festivals in the Americas : Performance, Representation, and the Making of Black Atlantic Tradition - Fromont, Cecile (Book collections on Project MUSE., 2019)
"Explores how, in the Americas, people of African birth or descent found spiritual and social empowerment in the orbit of the Church. Draws connections between Afro-Catholic festivals and their precedents in the early modern Christian kingdom of Kongo"--Provided by publisher